Same-sex marriage plebiscite - Foyle, Lindsay (2016)
Two people debating the cost and effectiveness of an Australian same-sex marriage plebiscite.
Title devised by cataloguer.
Inscriptions: "Lindsay"--Signed in ink below image; "24.08.2016"--In ink along side of image.
Part of the collection: Lindsay Foyle cartoon collection, 2008-2017.
Condition: Soiled.
Keywords: Plebiscite -- Australia -- Caricatures and cartoons; Same-sex marriage -- Australia -- Caricatures and cartoons; Australian wit and humor, Pictorial; Australia -- Politics and government -- 21st century -- Caricatures and cartoons; Australia -- Social conditions -- 21st century -- Caricatures and cartoons